In Memoriam - CPH 35(2), (Czasopismo Prawno-Historyczne, 1983)
Kazimierz Kolańczyk 1915-1982 (Władysław Rozwadowski) ... 237 Gerard Kuleczka 1934-1983 (Władysław Rozwadowski) ... 241 Jerzy Sliwowski 1907-1983 (Stanisław Salmonowicz) ... 243